The impact of hypoxia on psychological and cognitive functioning in high-altitude climbers - Zamirska, Wiktoria; Hornig, Nadia; Kołodziej, Aleksandra; Cieplak, Aleksandra; Czyżewicz, Zuzanna (Journal of Education, Health and Sport, 2025)
Introduction and purpose: This study aims to investigate the psychological and cognitive effects of hypoxia in high-altitude climbers, with a focus on specific psychological outcomes such as anxiety, hallucinations, and depression, and cognitive impairments, including memory deficits and impaired decision-making. The scope encompasses both acute and chronic exposure to high-altitude conditions, examining how hypoxia, in conjunction with environmental stressors such as cold, isolation, and physical exertion, impacts neurological function. The research seeks to elucidate the underlying mechanisms, including hypoxia-induced changes in cerebral oxygenation, neurotransmitter activity, and metabolic dysregulation, and their relationship to observed symptoms. Material and methods: An extensive examination of articles published in scientific journals was carried out using online research platforms databases, i.e. PubMed, Google Scholar, using key words contained in ‘Medical Subject Headings’ MeSH in appropriate configurations. Description of the state of knowledge: Published data indicate that prolonged high-altitude exposure impairs cognitive performance, particularly in areas such as attention, memory, and inhibitory control. These deficits are linked to hypoxia-induced oxidative stress, mitochondrial dysfunction, and structural brain changes. However, certain cognitive domains, such as perceptual processes and problem-solving abilities, appear to remain relatively unaffected by high-altitude conditions. Conclusions: Prolonged exposure to high altitudes detrimentally impacts cognitive performance. The most significant impairments are observed in psychomotor function and long-term memory. Perceptual processes, inhibitory control, and problem-solving skills are largely preserved. Further research is needed to explore individual variability and long-term adaptations to these environments.